(untitled) (Law and world, 2025)
Human safety (HS) is a relatively new doctrine that emerged at the end of the 20th century. It arose from the need to address global threats and to better understand worldwide problems. Human safety is a human right; it refers to the safety of people and communities, as opposed to that of states. The concept of human security recognizes several dimensions of safety, including freedom from fear, freedom from want, and freedom from indignity. Our study concerns the concepts of individual entitlements and individual safety, which are strongly supported in the discourse of international law. The safety of individuals has long been a central concern of the global community, first through the League of Nations and later under the United Nations. The concept of universal individual entitlements has opened the way for new rules in international law. Safeguarding these basic entitlements is no longer solely the responsibility of an individual’s state; it has become a shared interest of the entire international community. From this perspective, we call for recognizing the concept of individual safety as a customary rule capable of stopping the continuous attacks on humanity. Keywords: Human safety (HS), emergence, international law, aggression, international community, cooperation. Introduction The ideological struggle imposed by the Cold War, along with the threat of nuclear weapon use, has given way to more fundamental but no less significant concerns. The scourges of disease, hunger, crime, political repression, natural disasters, and terrorism have become an integral part of individuals’ daily realities. The focus of our research centers on two concepts that warrant clear definition: human entitlements (HR) and human safety (HS), the latter progressively emerging in the global discourse on the safeguarding of fundamental individual entitlements and individual dignity. In this context, the concept of the “universalization of individual entitlements” has paved the way for the emergence of a new norm in international law, whereby the safeguarding of an individual’s fundamental entitlements no longer rests solely with the authority of the state of which they are a national, but concerns the global community. Thus, the question arises as to whether the emergence of the concept of human safety (HS) as a new customary rule could generate sufficient practice to curb the recurrent violations against humanity. Methodology The study relies on a doctrinal legal analysis of primary international instruments (UN Charter, Universal Declaration of Human Rights, ICCPR/ICESCR, Geneva Conventions and Additional Protocols) and “soft law” documents (ICISS/R2P reports, UNDP/CHS frameworks). It also applies the historical method to trace the evolution from state-centric security to the concept of human security. In addition, a comparative policy analysis is employed to assess regional frameworks (EU, AU, Arab League) and institutional practices (UN Security Council, IMF/World Bank). The article combines descriptive and analytical synthesis, drawing on primary sources (international treaties, UNGA and UNSC resolutions, ICJ jurisprudence such as the Nicaragua case) and authoritative academic and agency reports, to formulate normative recommendations on codifying and operationalizing human security. The research does not use quantitative empirical methods; its focus is on conceptual delimitation (HS–HR; HS–R2P) and policy implications. 1. Clarification of the Concepts of Human Safety (HS) and Human Entitlements (HR) 1.1 The naturalization of man and his entitlements The notion of HS and HR stems from natural law theory as articulated by Grotius and is defined as a set of prerogatives inherent to every individual. According to Nicolas Valticos, “the concept of HR extends beyond the entitlements of individuals to encompass entitlements that man can and must enjoy either directly or through the communities to which he belongs”. Furthermore,[1] Amartya Sen adds that “The concept of HR is fundamentally normative, which means that it is not clear which specific freedoms are so important that society must recognize, safeguard, and promote them as HR. This is where the idea of HS can really help by showing how important it is to not have basic factors of unsafety, both new and old”.[2] In other words, HS redirects the global safety discourse toward the core of individual dignity, the recognition of public freedoms, inherent individual entitlements, and the responsibilities of states and intergovernmental organizations to ensure the effective respect of these entitlements. Indeed, HR has historically been established with reference to the natural right to safety; therefore, all states are required by law to abide by their normative principles, whether they are in conflict or at peace. A significant development is the emergence of a universally recognized principle, abstract in nature, yet endowed with absolute value: individual dignity. It represents the primary and fundamental intuition underlying HR and serves as the foundational reference that gives meaning to all other entitlements. It is this principle that legitimizes the very concept of HR.[3] According to Yves Madiot, HR are subjective entitlements that reflect, within the legal framework, the natural principles of justice that underpin the person.[4] In this regard, the Universal Declaration of HR (UDHR) of 1948 rightly asserts that “All people are born free and equal in entitlements and dignity, and they all have reason and conscience”.[5] It is based on this premise regarding the universal attributes of individual nature that a new understanding of a decent life has been shaped. These shared attributes translate into common needs inherent to the individual person and dignity, capable of ensuring the conditions necessary for a decent life. Regarding these needs intrinsic to the individual being, two main categories can be distinguished, corresponding to the first two generations of HR: fundamental freedoms (linked to the respect of civil and political entitlements) and a minimum level of economic safety, or subsistence[6] (guaranteed by the respect of economic entitlements). Without the fulfillment of these universal primary needs, individual dignity is difficult to conceive.[7] It is observed that the concept of HR encompasses a range of fundamental entitlements essential for a minimally decent life, Including, The rights to life, personal safety, including physical integrity, freedom from torture and other cruel, inhuman, or degrading treatment, equality before courts and tribunals, freedom from slavery, protection from systematic and harmful discrimination and persecution, and freedom of thought, conscience, and religion are just a few examples; and, finally, the right to property. Regarding economic entitlements,[8] it is clear that the concept of HR is dynamic and evolving, with the list and scope of these entitlements expanding as new entitlements are frequently added to existing ones. The question then arises: can HS be considered one of these entitlements? 1.2 The concept of human safety (HS) 1.2.1 Definition of the concept According to the Robert dictionary, safety is defined as the absence of actual danger, poverty, and any apprehension. The concept of HS is therefore founded on the principles of individual emancipation liberating individuals from fear and want, and social justice.[9] However, the initial idea of HS dates to the eighteenth century, when thinkers had already developed ideas concerning the safeguarding of individuals. At the global level, controversy remains intense. HS may be perceived as reflecting a global willingness to intervene, potentially disregarding the principle of state sovereignty when populations are in distress.[10] It is important to emphasize that this concept intensifies the debate surrounding one of the most contentious issues in global politics since the end of the Cold War: the “right or duty of humanitarian intervention”.[11] This issue confronted the global community in the early 1990s in response to the tragedies in Kurdistan, Somalia, Rwanda, and the former Yugoslavia. The debate on humanitarian intervention gained renewed prominence in the 1990s, particularly in the wake of crises in Rwanda and the former Yugoslavia, and was strongly advanced by French jurist Mario Bettati, who theorized the “right of intervention” as a novel transformation of the global order.[12] The concept revitalizes and enriches this debate by providing new foundations, which have contributed to the emergence of a developing normative framework embodied in the “Obligation to Safeguard”.[13] This idea says that sovereign states must safeguard their citizens from disasters that could have been avoided. If they can’t or won’t do this, the global community is responsible for doing so.[14] Recent scholarship reinforces this link: as Lau (2023) argues, operationalizing Human Security provides the analytical lens to detect risks to individuals, while the Responsibility to Protect supplies the political and legal duty to act upon those risks, thereby making the two concepts mutually reinforcing in both theory and practice.[15] The reports of the Global Commission on Intervention and State Sovereignty (ICISS) in 2001 introduced an innovative approach by seeking to resolve the theoretical debate between proponents of state sovereignty and advocates of intervention for civilian protection purposes.[16] In this context, can we assert that the obligation to safeguard, a necessary complement to the concept of HS, is intrinsically linked to the exercise of state sovereignty?[17] As a corollary to this premise, what are the criteria or conditions that objectively qualify the obligation to safeguard as a guiding principle for the implementation of such safety? 1.2.2 Birth and evolution of “human safety” (HS) The concept of safety lies at the foundation of modern state theory, particularly since the primary mission of the state is to safeguard members of the community, who, in return, owe it allegiance.[18] The right to safety is enshrined in Article 2 of the French Declaration of the Entitlements of Man and of the Citizen of 1789, affirming it as a natural and inalienable right.[19] The notion of safety was also central to a broad spectrum of philosophical discourse and to principles governing warfare. 1.3 Philosophical origins of human safety (HS) The initial conception of HS dates to the eighteenth century, when thinkers began to focus on the safeguarding of individuals. Many fundamental principles of HS draw on the reflections of Montesquieu, Rousseau, Smith, and Condorcet. Montesquieu emphasized liberty and the subjective entitlements of individuals rather than the safety provided by the state. For Adam Smith, safety meant safeguarding against “violent and sudden attacks upon the person or property”.[20] Condorcet described a social contract in which the safety of individuals was the foundational principle; in his view, if individuals live in fear, they cannot effectively participate as members of a political community.[21] However, these liberal convictions were not universally accepted. Thinkers such as Hobbes, Kant, and Grotius argued that the state’s monopoly on violence was the best means to end anarchy and prevent the law of the strongest from prevailing. For Hobbes, safety is synonymous with civil peace, under whose safeguarding the parties to the “social contract” enjoy their natural entitlements.[22] He argued that the state of nature was essentially a form of anarchy characterized by the domination of the strong over the weak, ultimately resulting in a perpetual state of war. Everyone is driven by a desire for power and the capacity to ensure self-preservation. Indeed, the primary purpose of the social contract is to escape this anarchic condition and guarantee safety.[23] According to Rousseau, however, the state of nature is portrayed in a more peaceful light. Man enjoys perfect freedom, and the exercise of this freedom by each individual leads to equality. For Rousseau, the establishment of civil society necessarily requires the conclusion of a “social contract” that serves not only to ensure safety for individuals but also to create a political society. Moreover, the social contract represents a voluntary submission to a law to which all have consented, as everyone retains a portion of sovereignty.[24] Kant was worried about the role of the state in keeping people safe. He imagined a higher authority: a world society based on the moral duty of the common good for its member nations. Grotius thought that the shared interests of independent states should safeguard everyone.[25] It can be said that the influence of these philosophical currents on the notion of HS is reflected in early treaties concerning the safeguarding of individuals, particularly the Geneva Conventions of April 24, 1863, which represented the first attempts to codify the laws and customs of war. From traditional safety to human safety (HS) Historically, safety primarily depended on relations between groups of states. In this traditional framework, the concept of the balance of power played a critical role in ensuring the safety of populations. States were viewed as rational entities, and safety was understood chiefly as safeguarding against invading armies.[26] These ideas were incorporated into the Covenant of the League of Nations, which further developed the concept of safety, later upheld by the United Nations. The UN legally prohibited any state from resorting to force in global relations for the first time (Articles 2 and 4). Indeed, the traditional conception of safety remained essentially military and state-centric until the 1980s.[27] Following the fall of the Berlin Wall and the end of the Cold War, the acceleration of economic globalization prompted a reevaluation of the meaning of safety.[28] As Durand (2003) observes, this shift illustrates the coexistence of different approaches to security—state-centered, military definitions on the one hand, and human-centered, multidimensional perspectives on the other.[29] This new perspective calls for addressing not only the physical safety of individuals but also their economic and social well-being, as well as respect for their dignity and values as individual beings.[30] Consequently, the concept of safety is grounded in the principles of individual emancipation by “liberating from fear and want” and social justice.[31] Thus, the focus has shifted from state safety to the safety of individuals. 1.4 Human safety (HS) in its broad and narrow senses Since the last decade of the 1900s, Kofi Annan, the Secretary-General of the United Nations, has talked about making the idea of HS clearer in his Report on the Organization’s Activities. He said that it is no longer enough to say that collective safety is just the absence of armed conflict, whether it is between countries or within a country. HR abuses, huge population movements, global terrorism, the AIDS pandemic, drug and arms trafficking, and environmental disasters all directly threaten our safety. This means we need to work together on a lot of different issues.[32] Within this context, the concept of “HS” centers the individual in the analysis, focusing on threats to the individual’s well-being and physical safety.[33] It makes clear that the goal of HS is to safeguard the most important parts of people’s lives in a way that makes it easier for people to exercise their entitlements and grow.[34] The broadest definition of HS was formulated in 1994 by the United Nations Development Programme (UNDP), Jorge Nef, and the Commission on Human Safety (CHS). A key point emphasized by the UNDP is the dual focus on first, safeguarding against chronic threats such as famine, disease, and repression; and second, safeguarding against sudden, violent events that disrupt everyday life.[35] In this UNDP definition, HS is linked to seven dimensions, each corresponding to specific types of threats: Economic stability, threatened by poverty; Food stability, threatened by famine; Health safety, threatened by injury and disease; Environmental safety, threatened by pollution, environmental degradation, and resource depletion; Personal stability, threatened by various forms of violence; Political safety, threatened by repression; Community safety, threatened by instability and civil unrest.[36] Regarding the second point, HS in its broader sense is reflected in the priority given to the “vital essentials of individuals”, a fundamental element that distinguishes HS from individual development.[37] As David and Rioux (2001) argue, the notion of human safety represents a new conception of international relations, one that redefines global security by centering the individual rather than the state.[38] It should be emphasized that HR and HS exist in a synergistic relationship. HS helps identify entitlements that are at risk in a specific context, while HR provides guidance on how HS should be safeguarded.[39] This relationship was articulated during a seminar organized in 2001 in Costa Rica by the CHS, in response to the call of the United Nations Millennium Summit by Secretary-General Kofi Annan. Addressing two major themes, the unsafety caused by conflict and violence on one hand, and the connections between safety and development on the other Commission was tasked with developing a concept of HS that could serve as a practical tool for the development and implementation of policies. Based on this mandate, the Commission was asked to propose a concrete program of recommendations to address the most critical and widespread threats to HS.[40] After this call, the CHS said that “HR and the qualities associated with individual dignity make up a conceptual reference point and a normative framework that are necessary to comprehend and implement the HS notion”. Likewise, whilst recognizing that the standards and tenets of global civilian protection law are crucial elements in understanding HS, the Commission emphasized that HS cannot be confined solely to current or past armed conflict situations. Rather, HS is a concept that must be applied universally.[41] Furthermore, recent publications by the UN Office on Human Security underscore new debates and implementation trends in Human Security, emphasizing interconnected crises—such as climate change, inequalities, displacement, health-system fragility—and reaffirming the necessity for global cooperation to address them. For instance, UNDP’s 2024 informal plenary meeting highlighted how a “human security lens” can help in formulating early warning systems and structuring policy responses that integrate prevention, protection, and dignity.[42] As highlighted by the UNDP (2022) Special Report on Human Security: New Threats to Human Security in the Anthropocene, “people’s sense of safety and security is at a low in almost every country, including the richest countries, despite years of upward development success”. This finding illustrates that despite decades of development progress, insecurity remains pervasive, reinforcing the urgency of embedding HS as both an analytical lens and a guiding principle of international cooperation.[43] However, the narrow interpretation of the concept of HS focuses primarily on violent threats directed at individuals. This limited definition constrains the scope of HS to specific parameters, such as drug trafficking, small arms proliferation, landmines, ethnic conflicts, terrorism, individual trafficking, or state failure, as noted by former Canadian Foreign Minister Lloyd Axworthy. Addressing these threats relies chiefly on diplomatic resources, economic persuasion, intelligence gathering, and information technologies.[44] In fact, most significant advancements made under the banner of HS have been based on this restricted understanding. Examples include the Mine Ban Treaty, the establishment of the Global Criminal Court (ICC), as well as recent global initiatives concerning child soldiers, small arms control, and the role of non-state actors in conflicts, all of which reflect the narrow interpretation of the HS principle.[45] Ultimately, it is important to observe that the globalization of risks and threats, the complexity of conflicts, terrorist attacks, and mass civilian massacres have driven the global community to develop legal instruments addressing three key dimensions of the issue: The safety of populations as a legitimate legal concern; Safeguarding as an obligation that is both moral and legal; Obligation as a political principle intrinsically linked to the exercise of sovereignty.[46] 2. The Global Safeguarding of Human Entitlements (HR): An Obligation That Is Both Moral and Legal 2.1 Human safety (HS) in global relations 2.1.1 Human safety (HS) as a new principle of global cooperation HS can therefore be understood as a fundamental link between the various objectives of the United Nations, creating an obligation for Member States to cooperate in advancing these goals coherently. On this basis, HS helps identify HR that may be at risk in specific situations. It provides new tools and drives significant changes in global practice. In this regard, strengthening global peace is a universal necessity in addressing the challenges of safety and development. It follows that the participation and engagement of all members of the global community, whether states, non-governmental organizations, or other civil society actors, are essential obligations to achieve a HS framework.[47] It is important to note that several norms, principles, and institutions are already established; for example, civilian protection assistance during natural disasters and the safeguarding of war victims are key components of enhancing HS worldwide. Thus, it is crucial to emphasize that this concept is shaping a body of global law that will no longer regulate solely the relations between states under a neutral respect for state sovereignty but will instead defend values and solidarities that prioritize the sovereignty of individuals over that of the state.[48] In other words, the concept of HS serves as a framework for reevaluating the contemporary meaning of sovereignty, introducing an emerging new logic within global law. According to the 1994 Individual Development Report, “the time has come to shift from a conception of safety centered on conflicts between countries over territorial integrity to one that addresses the insecurities arising from the daily concerns of the majority of the world’s population”.[49] One might argue that the notion of HS reverses the traditional logic of state sovereignty, transforming governments into instruments of citizens aimed at enhancing the well-being of the population.[50] Sovereignty no longer simply denotes the imposition of power but extends to the obligation to safeguard a people within a territory through respect for the law and the effective functioning of the justice system, alongside the reconstruction of the socio-economic framework of the society concerned. To achieve these objectives, the ICISS[51] Sovereignty encourages states to adopt the principle of the obligation to safeguard, according to which the global community may intervene to prevent mass violations of HR or to alleviate the suffering of victims in the event of conflict or natural disaster. These ideas were already articulated by the United Nations Secretary-General in his March 2000 report, where he stated: “While civilian protection intervention constitutes an unacceptable infringement on sovereignty, how should we respond to situations such as those witnessed in Rwanda or Srebrenica, where there have been blatant, massive, and systematic violations of HR, in direct contradiction to the fundamental principles on which our shared humanity is founded?”[52] Similarly, the 2005 World Summit Outcome Document introduced a renewed vision of HS and established a collective global obligation to safeguard HR in the face of genocide, ethnic cleansing, and crimes against humanity.[53] It is important to emphasize that this obligation primarily lies with states; however, in cases of unwillingness or incapacity to act, the global community may step in to address these failures and intervene to halt widespread violations of HR.[54] Thus, respect for HR and humanitarian law forms the foundational pillars of the concept of HS. “As highlighted by the Global Centre for the Responsibility to Protect, ‘R2P is essentially about preventing and protecting people from the most heinous atrocity crimes – genocide, war crimes, ethnic cleansing and crimes against humanity… The grim reality of today’s ongoing crises is a stark reminder of the need to redouble efforts to effectively implement the responsibility to protect”.[55] 2.1.2 The legal framework of the concept of human safety (HS) The Human Safety Network (HSN) currently lacks formal sources that would integrate the concept into positive law, but it is possible to link the concept to formal global legal instruments, such as: United Nations instruments related to peace and human safety (HS) The safety of individuals has always been a central concern for the global community. Initially through the League of Nations and now under the United Nations, which, in its preamble, explicitly identifies HS as one of its core objectives in its founding resolution. The Charter states: “We, the people of the United Nations, are determined to safeguard future generations from the horrors of war, which has brought great sadness to people twice in our lifetime, and to reaffirm our faith in basic HR and keep the peace and safety of the world...” It goes on to state that one of its main objectives is “keeping the peace and safety around the world, and to do that, taking effective collective steps to stop and remove threats to the peace, stop acts of aggression or other violations of the peace, and settle or change global disputes or situations that could lead to a breach of the peace in a way that follows the rules of justice and global law”.[56] This demonstrates that HS is closely associated with global peace, as the terms “safety” and “peace” are used interchangeably in the Charter’s preamble. Accordingly, HS at this level may be understood as synonymous with collective safety. Global Human Entitlements (HR) Law The globalization of HR has blurred the traditional distinction between domestic legal orders and global legal frameworks. Numerous legal instruments have been adopted for this purpose, among which the UDHR of December 10, 1948, stands as a cornerstone. Article 3 of the UDHR enshrines the notion of individual safety with the provision: “Everyone has the right to life, liberty and safety of person”. In this context, Article 28 states that “Everybody has the right to a social and global order that fully realizes the freedoms and rights outlined in this Declaration”. There is a notable connection between the “social level” and the “global level”, and this provision is presented as a common ideal to be achieved by all peoples and nations. Two legally binding global agreements were made in 1966 to reaffirm the Universal Declaration. One was about civil and political entitlements, and the other was about economic, social, and cultural entitlements.[57] More than 140 countries have signed these two agreements as of today. These documents, along with the Universal Declaration, make up the Global Bill of HR and are the basis for global HR law and many other global and regional treaties.[58] The Global Covenant on Civil and Political Entitlements guarantees, among other entitlements, the right to life, liberty, and prohibits torture. In addition to rights to social safety, education, and other benefits, the Global Covenant on Economic, Social, and Cultural Entitlements outlines everyone’s right to labor in fair and advantageous circumstances, including the ability to organize and join trade unions and go on strike. 2.1.3 Norms of global humanitarian law Global humanitarian law (IHL), also known as the “law of war” and more recently the “law of armed conflict”, is a branch of global law. It developed over centuries, initially through temporary agreements between conflicting parties and, from 1864 onward, through global conventions.[59] IHL applies during interstate armed conflicts or those occurring within the borders of a state. Its purpose is to safeguard individuals, whether they are parties to the conflict. The establishment of the Global Committee of the Red Cross (ICRC), the Hague Conventions of 1899 and 1907, the four Geneva Conventions of 1949, and the two Additional Protocols of 1977 collectively form a body of global rules, conventional and customary, primarily aimed at addressing humanitarian issues directly resulting from global or non-global armed conflicts.[60] As Biad (2006) underlines, international humanitarian law represents not only a codified system of rules governing armed conflict, but also a comprehensive framework that reflects the evolution of humanitarian values in international law.[61] The primary objective of IHL is to safeguard persons who do not take part, or no longer take part, in hostilities (civilians). It imposes numerous obligations and, consequently, individual criminal obligation for violations of the Geneva Conventions and Additional Protocol I. As Buirette and Lagrange (2008) note, the humanitarian purpose of IHL extends beyond regulating hostilities, aiming primarily to preserve human dignity and limit suffering even amidst armed conflict.[62] Significant differences in formulation, the essence of certain rules under IHL, and the concept of HS is fundamentally aligned. Both aim to safeguard individual life from threats to the person as well as to the essential goods necessary for survival. As Bettati (2012) observes, international humanitarian law constitutes not only a body of rules applicable in armed conflicts, but also a normative framework that directly reinforces the safeguarding of human dignity and fundamental rights.[63] Regarding the second point on HS, it is important to emphasize that under IHL, there exists a right to humanitarian assistance. Humanitarian relief efforts that are impartial in nature cannot be condemned as interference or violations of a state’s national sovereignty. In its 1986 ruling on the Military and Paramilitary Activities in and against Nicaragua case, the Global Court of Justice recognized that the provision of humanitarian aid does not constitute an unlawful intervention in the internal affairs of another state, provided it is limited to the purposes established by the practice of the Red Cross.[64] The most significant development in humanitarian law is the recognition that the use of war is no longer a lawful means of resolving conflicts, and that resorting to force itself constitutes a violation of HR.[65] This principle was explicitly affirmed during the 1968 Tehran Conference on HR: “War is the opposite of peace, and peace is the only way to fully respect HR”.[66] It is clear that humanitarian law is still a good way to safeguard people during armed conflict, and this safeguarding is still needed because, unfortunately, the law that says force can’t be used has not stopped armed conflicts from happening.[67] The true turning point that initiated the convergence of humanitarian law and HR law occurred at the 1968 Global Conference on HR in Tehran. It was at this conference that the United Nations first addressed the issue of applying HR in the context of armed conflict.[68] The true turning point that initiated the convergence of humanitarian law and HR law occurred at the 1968 Global Conference on HR in Tehran. It was at this conference that the United Nations first addressed the issue of applying HR in the context of armed conflict. As Doswald-Beck and Vité (1993) emphasize, this convergence represents a complementary evolution, whereby humanitarian law and human rights law both seek to safeguard human dignity amidst the realities of armed conflict.[69] 2.2 Human safety (HS) as a rationale for the proliferation of global interventions Given that HS encompasses multiple domains, several global institutions are involved in its implementation, notably the United Nations Security Council and global economic institutions. 2.2.1 Intervention by the UN Security Council The broadening scope of global safety is evident in the increasingly expansive interpretation by the Safety Council of what constitutes a “threat to global peace and safety”, which now includes, among other elements: the possibility of intervention in internal conflicts, reference to HR violations, and the consideration of non-state actors as targets of Safety Council resolutions imposing sanctions under Chapter VII (such as terrorist groups and rebel factions). Interpretative practice regarding Article 39 of the UN Charter reveals a tendency to regard internal conflicts involving massive HR violations and serious breaches of IHL as conflicts that threaten global peace and safety.[70] It is important to first recall that the concept of HS embodies a global willingness to intervene in the internal affairs of states and the potential to alter the traditional framework of national sovereignty and its corollaries, the principles of non-use of force and non-intervention in the internal affairs of a sovereign state. As Conforti (1993) underlines, the Security Council retains broad discretionary power in determining what constitutes a “threat to the peace, a breach of the peace, or an act of aggression” under Article 39 of the UN Charter.[71] This form of intervention has been codified by the UN Security Council and is grounded in the UDHR of 1948. If a state is unable or unwilling to safeguard its citizens, the global community may assume that obligation. The recognition of the imperative to safeguard the person has led to the establishment of a right to humanitarian intervention, whereby states and state organizations are authorized to provide emergency assistance to populations in distress. In the concluding document of the 2005 World Summit, Member States explicitly recognized that “According to Chapters VI and VIII of the Charter, the United Nations is responsible for protecting people from genocide, war crimes, ethnic cleansing, and crimes against humanity by using the right diplomatic, humanitarian, and other peaceful means”. The early 1990s were marked by a sense of optimism reflected in discussions about a “new world order”. For illustration, one can cite the cases of Iraq in 1991, Bosnia and Herzegovina in 1992, Somalia in 1992, Rwanda in 1994, and more recently Libya in 2011 and the Central African Republic in 2013. In all these instances, the Safety Council condemned violations of HR and humanitarian law committed during the armed conflicts and called for accountability to be established.[72] The Safety Council also got an active role in stopping impunity for those who commit genocide, war crimes, crimes against humanity, and aggression when the Rome Statute was passed. The Rome Statute says that the Safety Council may send cases to the ICC if it seems like one or more of these crimes have been committed. This is allowed under Chapter VII of the United Nations Charter.[73] In Resolution 1593 (2005), the Security Council used its power to say that the situation in Sudan’s Darfur area was a danger to global peace and safety and sent the matter to the Prosecutor. Ultimately, it can be said that the Safety Council, as the UN’s executive body endowed with coercive powers, holds a central obligation in implementing the United Nations’ fundamental principles, particularly the obligation to safeguard civilian populations and prevent egregious HR violations that amount to genocide, crimes against humanity, or war crimes. As Gallagher (2025) emphasizes, while the “death of R2P” narrative has gained traction in policy and academic debates, such claims are misleading: the norm continues to evolve institutionally and politically, demonstrating resilience rather than disappearance.[74] Yet, even among states that support R2P rhetorically, sustaining it under conditions of geopolitical polarization presents significant challenges. “Thus, while small states certainly can find arenas where R2P can be promoted, they cannot be seen as guarantors of the norm”.[75] 2.2.2 The involvement of global economic institutions Since 1990, the number of people suffering from persistent hunger has increased by over 80 million, alongside growing food unsafety. Meanwhile, due to emergencies triggered by conflicts and a rise in natural disasters, the demand for food aid has continued to grow.[76] Institutions such as the World Bank, the Global Monetary Fund (IMF), the Organization for Economic Co-operation and Development (OECD), and the World Trade Organization (WTO) increasingly incorporate considerations related to HS within their normative frameworks and operational activities. However, rather than using the term “HS”, they tend to refer to the “social consequences of economic policies” or “individual development”.[77] The Bretton Woods institutions refer more explicitly to the concept of individual development rather than HS. They now argue that effectively combating poverty requires not only promoting economic growth but also addressing the political and social inequalities that perpetuate poverty. In line with the objectives of the new generation of World Bank programs, there is a call for the participation and empowerment of poor countries.[78] In its 2005 report on the Millennium Development Goals, the World Bank urges wealthy countries to aim higher and improve their political programs and governance measures concerning aid, trade, and debt relief for developing countries. The Bank’s work focuses on identifying the everyday concerns of those classified as “poor” according to the Individual Development Index, and on examining their adherence to democratic principles and respect for civil and political entitlements.[79] Conclusion The issue of HS can therefore be seen as a fundamental linkage among the various goals of the United Nations, and as an obligation for Member States to cooperate in advancing these goals coherently. On this basis, HS helps to identify HR who are potentially at risk in a given situation. In this regard, strengthening global peace is an essential response to the intertwined challenges of safety and development. It follows from this premise that the participation and engagement of all members of the global community—whether states, non-governmental organizations, or other civil society actors—is imperative to achieving an effective HS framework. At the same time, more concrete commitments are required. UN Member States should reinforce the principle of Human Safety within binding international treaties and regional frameworks, such as the European Union, the African Union, and the Arab League. Specific institutional mechanisms should also be established to safeguard HS in practice, ensuring accountability and effective implementation. Moreover, Human Safety must be mainstreamed within international economic institutions, such as the IMF and the World Bank, where it should serve as a core criterion for evaluating policies and programs. Finally, further research should focus on the legal codification of HS, the comparative analysis of regional practices, and in-depth case studies in specific contexts—particularly Africa, the Middle East, and the Caucasus—where the operationalization of Human Safety remains both urgent and contested. References Scientific Literature: Addi, L. (n.d.). The concept of security tested by the new global order: The case of Algeria. Available at: <http://www.algeria-watch.org/fr>; Agence Universitaire de la Francophonie. (n.d.). Human security and the obligation to protect: The international humanitarian order in question. Paris: Éditions des Archives Contemporaines; Bettati, M. (1996). The right of intervention: Changes in the global order. Paris: Odile Jacob Editions; Bettati, M. (2012). Humanitarian law (1st). Paris: Dalloz Editions; Bélanger, M. (2002). Global humanitarian law. Paris: Gulino Éditeur; Biad, A. (2006). Global humanitarian law (2nd). Paris: Ellipses Editions; Boyle, K., Simonsen, S. (2004). Human security, human rights, and disarmament. In Human rights, human security, and disarmament (Disarmament Forum No. 3, UNIDIR); Buirette, P., Lagrange, P. (2008). Global humanitarian law. Paris: La Découverte Edition ; Conforti, B. (1993). The discretionary power of the Security Council in determining a threat to the peace, a breach of the peace, or an act of aggression. In Proceedings of the Hague Academy of International Law Colloquium (July 21–23, 1992). Dordrecht/Boston/London: Martinus Nijhoff Publishers; David, C. P., Rioux, J.-F. (2001). The concept of human security. In Human security: A new conception of global relations (Raoul Dandurand Collection, L’Harmattan Edition); Doswald-Beck, L., Vité, S. (1993). Global humanitarian law and human rights law. International Review of the Red Cross, Geneva; Doswald-Beck, L., Vité, S. (1993). International humanitarian law and human rights law. International Review of the Red Cross, 33(293); Durand, D. (2003). The different approaches to security (February). Institut IDRP. Available at: <http://www.institutidrp.org>. Gallagher, A. (2025). Farewell the Responsibility to Protect? International Affairs, 101(2), Oxford University Press, pp. 483–502. Available at: <https://doi.org/10.1093/ia/iiaf010>; Global Commission on Intervention and State Sovereignty (ICISS). (2001). The responsibility to protect: Report of the International Commission on Intervention and State Sovereignty. International Development Research Centre. Available at: <https://www.iciss.ca/>; Hussein, K., Gnisci, D., Wanjiru, J. (2004). Security and human security: Presentation of concepts and initiatives – Key implications for West Africa. Sahel and West Africa Club; Krause, K. (2003). A critical and constructivist approach to security studies, p. 611. Available at: <http://www.afri-ct.org/IMG/pdf/krause2003.pdf>; Lau, R. K. S. (2023). Operationalizing human security: What role for the responsibility to protect? International Social Science Journal. Available at: <https://doi.org/10.1177/00208817231154054>; Letteron, R. (n.d.). The universality of human rights: Appearances and reality – The ideology of human rights in France and the United States. Available at: <http://www.diplomatie.gouv.fr>; Lowenthal, P. (2008–2009). Ambiguities of human rights. Droits fondamentaux, (7), p. 2. Available at: <http://www.droits-fondamentaux.org>; Madiot, Y. (1991). Human rights (2nd). Paris: Masson; Owen, T. (2004). On the difficulties and value of defining and assessing human security. In Human rights, human security, and disarmament (Disarmament Forum No. 3, UNIDIR); Pellet, A. (n.d.). Right of intervention or duty of humanitarian assistance? In P.P.S., La Documentation Française, No. 758–859; Ramel, F. (2001). Global economic institutions and human security: Toward a new security regime? In Human security: A new conception of global relations. Paris: L’Harmattan; Sen, A. (2003). Development, rights, and human security. In Human security now: Report of the Commission on Human Security, Paris: Presses de Sciences Po; Stensrud, E. E., Mennecke, M. (2024). On the 20th anniversary of the responsibility to protect: Can small states save R2P from failure and oblivion? Nordic Journal of Human Rights, 42(4). Available at: <https://doi.org/10.1080/18918131.2024.2426404>; Thibault, J.-F. (2013). On the obligation to protect threatened populations: The use of force and the possibility of justice. Québec: Les Presses de l’Université Laval; Ubeda-Saillard, M. (2011). The limits of the obligation to protect: Natural disasters. In Chaumette, A.-L., Thouvenin, J.-M. (Eds.), The obligation to protect, ten years later. Paris: A. Pedone Editions; Valticos, N. (1991). The concept of human rights in global law. In International law in the service of peace, justice and development: Essays in honour of Michel Virally, Paris: A, Pedone; Vézina, L.-P. (2010). The obligation to protect and humanitarian intervention: From the reconceptualization of state sovereignty to normative individualism (master’s thesis, University of Montreal, Faculty of Graduate Studies). Official documents and reports Délégation for Human Rights and Democracy. (2006). Human security: Clarification of the concept and approaches by global organizations – some reference points (Information document, January); (1789). Declaration of the Rights of Man and of the Citizen. Paris: National Constituent Assembly; Global Centre for the Responsibility to Protect. (2020). A Reflection on the Responsibility to Protect in 2020. Available at: <https://www.globalr2p.org/publications/a-reflection-on-the-responsibility-to-protect-in-2020/>; International Commission on Intervention and State Sovereignty. (2001). The obligation to protect (Report of the ICISS Sovereignty, December); International Committee of the Red Cross. (1863). Geneva Convention for the Amelioration of the Condition of the Wounded in Armies in the Field. Geneva: ICRC. International Committee of the Red Cross. (1949). Geneva Conventions of 12 August 1949. Geneva: ICRC; International Committee of the Red Cross. (1977). Additional Protocols I and II to the Geneva Conventions of 12 August 1949. Geneva: ICRC; International Conference on Human Rights. (1968). Resolution XXIII: Safeguarding of human rights in armed conflict. Tehran: United Nations; International Court of Justice. (1986). Case concerning military and paramilitary activities in and against Nicaragua (Nicaragua v. United States of America), merits, judgment. I.C.J. Reports 1986; San José Declaration. (2001). San José Declaration on Human Security. San José; (2022). Special Report on Human Security: New threats to human security in the Anthropocene. United Nations Development Programme. Available at: <https://hdr.undp.org/content/2022-special-report-human-security>; United Nations Development Programme. (1994). Human Development Report 1994, Paris: Economica Edition; United Nations General Assembly. (1948). Universal Declaration of Human Rights; United Nations General Assembly. (1966). International Covenant on Economic, Social and Cultural Rights; United Nations General Assembly. (2005). 2005 World Summit Outcome (A/RES/60/1). United Nations; United Nations Office on Human Security. (2024). Publications on human security. Available at: <https://www.un.org/humansecurity/publications-on-human-security/>; United Nations Trust Fund for Human Security. (2009). Application of the human security concept and the United Nations Trust Fund for Human Security. United Nations Office for the Coordination of Humanitarian Affairs; United Nations, Office of the High Commissioner for Human Rights. (2011). Global legal safeguarding of human rights in armed conflict. New York & Geneva: United Nations; United Nations. (1945). Charter of the United Nations; United Nations. (1998). Rome Statute of the International Criminal Court. United Nations Treaty Series, 2187, 3; United Nations. (2000). Report of the Secretary-General on the Activities of the Organization. Official Records of the Fifty-Fifth Session of the General Assembly, Supplement No. 1 (A/55/1). Footnotes [1] Valticos, N. (1991). The concept of human rights in global law. In International law in the service of peace, justice and development: Essays in honour of Michel Virally, Paris: A, Pedone, 483-491. [2] Sen, A. (2003). Development, rights, and human security. In Human security now: Report of the Commission on Human Security, Paris: Presses de Sciences Po, pp. xx-xx. [3] Lowenthal, P. (2008–2009). Ambiguities of human rights. Droits fondamentaux, (7), p. 2. Available at: <http://www.droits-fondamentaux.org>. [4] Madiot, Y. (1991). Human rights (2nd ed.). Paris: Masson, p. 26. [5] United Nations General Assembly. (1948). Universal Declaration of Human Rights, Article 1. [6] We refer here to the meaning given by Henry Shue regarding the content of subsistence, that is, having access to clean air, clean water, enough food, clothes, and shelter, as well as a basic public health preventative system. See: Vézina, L.-P. (2010). The obligation to protect and humanitarian intervention: From the reconceptualization of state sovereignty to normative individualism (master’s thesis, University of Montreal, Faculty of Graduate Studies), p. 65. [7] Ibid. [8] United Nations General Assembly. (1966). International Covenant on Economic, Social and Cultural Rights, Part III. [9] Délégation for Human Rights and Democracy. (2006). Human security: Clarification of the concept and approaches by global organizations – some reference points (Information document, January), p. 4. [10] David, C. P., Rioux, J.-F. (2001). The concept of human security. In Human security: A new conception of global relations (Raoul Dandurand Collection, L’Harmattan Edition), pp. 19–30. [11] Bettati, M. (1996). The right of intervention: Changes in the global order. Paris: Odile Jacob Editions. Pellet, A. (n.d.). Right of intervention or duty of humanitarian assistance? In P.P.S., La Documentation Française, No. 758–859, p. 133. [12] Bettati, M. (1996). The right of intervention: Changes in the global order. Paris: Odile Jacob Editions. [13] International Commission on Intervention and State Sovereignty. (2001). The obligation to protect (Report of the ICISS Sovereignty, December), paras. 2.21–2.33. [14] Délégation for Human Rights and Democracy. (2006), op. cit., p. 6. [15] Lau, R. K. S. (2023). Operationalizing human security: What role for the responsibility to protect? International Social Science Journal. Available at: <https://doi.org/10.1177/00208817231154054>. [16] Agence Universitaire de la Francophonie. (n.d.). Human security and the obligation to protect: The international humanitarian order in question. Paris: Éditions des Archives Contemporaines, p. 14. [17] Ibid. [18] Addi, L. (n.d.). The concept of security tested by the new global order: The case of Algeria. Available at: <http://www.algeria-watch.org/fr>. [19] Agence Universitaire of the Francophonie. (n.d.), op. cit., p. 22. [20] Owen, T. (2004). On the difficulties and value of defining and assessing human security. In Human rights, human security, and disarmament (Disarmament Forum No. 3, UNIDIR), pp. 17–18. [21] Ibid., p. 18. [22] Addi, L. (n.d.), op. cit., p. 1. [23] Letteron, R. (n.d.). The universality of human rights: Appearances and reality – The ideology of human rights in France and the United States, p. 150. Available at: <http://www.diplomatie.gouv.fr>. [24] Ibid, p.150. [25] Owen, T. (2004), op. cit., p. 18. [26] Ibid., p. 19. [27] Durand, D. (2003). The different approaches to security (February). Institut IDRP. Available at: <http://www.institutidrp.org>. [28] Ibid. [29] Durand, D. (2003), op. cit. [30] Délégation for Human Rights and Democracy. (2006), op. cit., p. 4. [31] Ibid. [32] United Nations. (2000). Report of the Secretary-General on the Activities of the Organization. Official Records of the Fifty-Fifth Session of the General Assembly, Supplement No. 1 (A/55/1). [33] Krause, K. (2003). A critical and constructivist approach to security studies, p. 611. Available at: <http://www.afri-ct.org/IMG/pdf/krause2003.pdf>. [34] Boyle, K., Simonsen, S. (2004). Human security, human rights, and disarmament. In Human rights, human security, and disarmament (Disarmament Forum No. 3, UNIDIR), p. 6. [35] United Nations Development Programme. (1994). Human Development Report 1994, Chapter 2: New dimensions of human security. Paris: Economica Edition, pp. 23-26. [36] Owen, T. (2004), op. cit., p. 20. [37] Délégation for Human Rights and Democracy. (2006), op. cit., p. 8. [38] David, C. P., Rioux, J. F. (2001), op. cit. [39] Boyle, K., Simonsen, S. (2004), op. cit., p. 6. [40] Délégation for Human Rights and Democracy. (2006), op. cit., p. 8. [41] San José Declaration. (2001). San José Declaration on Human Security. San José. [42] United Nations Office on Human Security. (2024). Publications on human security. Available at: <https://www.un.org/humansecurity/publications-on-human-security/>. [43] UNDP. (2022). Special Report on Human Security: New threats to human security in the Anthropocene. United Nations Development Programme. Available at: <https://hdr.undp.org/content/2022-special-report-human-security>. [44] Délégation for Human Rights and Democracy. (2006), op. cit., p. 10. [45] Ibid. [46] Agence Universitaire de la Francophonie. (n.d.), op. cit., p. 13. [47] Hussein, K., Gnisci, D., Wanjiru, J. (2004). Security and human security: Presentation of concepts and initiatives – Key implications for West Africa. Sahel and West Africa Club, p. 17. [48] Délégation for Human Rights and Democracy. (2006), op. cit., p. 11. [49] Agence Universitaire of the Francophonie. (n.d.), op. cit., p. 29. [50] Délégation for Human Rights and Democracy. (2006), op. cit., p. 11. [51] Global Commission on Intervention and State Sovereignty (ICISS). (2001). The responsibility to protect: Report of the International Commission on Intervention and State Sovereignty. International Development Research Centre. Available at: <https://www.iciss.ca/>. [52] Ibid. [53] Ubeda-Saillard, M. (2011). The limits of the obligation to protect: Natural disasters. In Chaumette, A.-L., Thouvenin, J.-M. (Eds.), The obligation to protect, ten years later. Paris: A. Pedone Editions, p. 28. [54] Thibault, J.-F. (2013). On the obligation to protect threatened populations: The use of force and the possibility of justice. Québec: Les Presses de l’Université Laval, p. 5. [55] Global Centre for the Responsibility to Protect. (2020). A Reflection on the Responsibility to Protect in 2020. Available at: <https://www.globalr2p.org/publications/a-reflection-on-the-responsibility-to-protect-in-2020/>. [56] United Nations. (1945). Charter of the United Nations, Article 1. [57] According to Article 11, paragraph 1 of the ICESCR, the “States the Covenant’s parties acknowledge that everyone has the right to a sufficient quality of living, which includes enough food, and they pledge to take the required actions to guarantee that this right is realized”. [58] Boyle, K., Simonsen, S. (2004), op. cit., p. 7. [59] Buirette, P., Lagrange, P. (2008). Global humanitarian law. Paris: La Découverte Edition, p. 33. [60] Bettati, M. (2012). Humanitarian law (1st ed.). Paris: Dalloz Editions; Bélanger, M. (2002). Global humanitarian law. Paris: Gulino Éditeur; [61] Biad, A. (2006). Global humanitarian law (2nd ed.). Paris: Ellipses Editions. [62] Buirette, P., Lagrange, P. (2008), op. cit. [63] Bettati, M. (2012), op. cit. [64] International Court of Justice. (1986). Case concerning military and paramilitary activities in and against Nicaragua (Nicaragua v. United States of America), merits, judgment. I.C.J. Reports 1986, p. 14, para. 243. [65] Doswald-Beck, L., Vité, S. (1993). Global humanitarian law and human rights law. International Review of the Red Cross, (800), Geneva, p. 14. [66] International Conference on Human Rights. (1968). Resolution XXIII: Safeguarding of human rights in armed conflict. Tehran: United Nations. [67] Doswald-Beck, L., Vité, S. (1993), op. cit., p. 14. [68] Ibid., p. 21. [69] Doswald-Beck, L., Vité, S. (1993). International humanitarian law and human rights law. International Review of the Red Cross, 33(293), pp. 94–119. [70] Conforti, B. (1993). The discretionary power of the Security Council in determining a threat to the peace, a breach of the peace, or an act of aggression. In Proceedings of the Hague Academy of International Law Colloquium (July 21–23, 1992). Dordrecht/Boston/London: Martinus Nijhoff Publishers, p. 53. [71] Ibid. [72] As an example, Security Council resolution 1019 (1995) concerning violations committed in the former Yugoslavia reads as follows: “urges that everyone involved fulfill their responsibilities in this respect and strongly condemns any abuses of human rights and global humanitarian law that have occurred on the former Yugoslavian territory. Also, S/RES/1034 (1995) resolution. [73] United Nations, Office of the High Commissioner for Human Rights. (2011). Global legal safeguarding of human rights in armed conflict. New York & Geneva: United Nations, pp. 106-107. [74] Gallagher, A. (2025). Farewell the Responsibility to Protect? International Affairs, 101(2), Oxford University Press, pp. 483–502. Available at: <https://doi.org/10.1093/ia/iiaf010>. [75] Stensrud, E. E., Mennecke, M. (2024). On the 20th anniversary of the responsibility to protect: Can small states save R2P from failure and oblivion? Nordic Journal of Human Rights, 42(4), pp. 435–444. Available at: <https://doi.org/10.1080/18918131.2024.2426404>. [76] United Nations Trust Fund for Human Security. (2009). Application of the human security concept and the United Nations Trust Fund for Human Security. United Nations Office for the Coordination of Humanitarian Affairs. [77] Ramel, F. (2001). Global economic institutions and human security: Toward a new security regime? In Human security: A new conception of global relations. Paris: L’Harmattan, p. 189. [78] Délégation for Human Rights and Democracy. (2006), op. cit., p. 26. [79] Ibid., p. 27.